Facile synthesis of superconducting NbN nanoparticles. Issue 1 (January 2015) - Liu, Xianguo; Zhou, Guiping; Wing Or, Siu; Ran, Songlin; Sun, Yuping
Abstract: Face-centered cubic NbN (δ-NbN) nanoparticles have been synthesized by arc-discharging Nb ingot in a mixture of H2, Ar and N2 . The presence of δ-NbN is attributed to the high surface energy of nanoparticles and the nonequilibrium condition during the arc-discharging process. NbN nanoparticles are of irregular spherical shape, and the diameter distribution is from 5 to 15 nm. The critical temperature of superconducting transition in NbN nanoparticles is determined to be 15.1 K, which is slightly less than that for the bulk counterpart. The difference is attributed to the fact that the size of NbN nanoparticles is comparable with the coherence length of NbN.